Heavy Metal Resistances of Enterobacteriaceae from Aksu River (Turkey) Polluted with Different Sources - Toroglu, Sevil; Dinτer Sadik (Asian Journal of Chemistry, 2010)
In this study, the heavy metal contamination of Aksu river, which have urban, industrial and agricultural effluents and also resistance frequency against heavy metals, belonging to Enterobacteriaceae (representative of the human and animal commensal flora) (66 isolates) and Pseudomonas sp., (only one isolate) were investigated. The samples were taken from five different sample stations settled on Aksu river and its brooks. The level of heavy metals, namely nickel, cadmium, copper and chromate, in water samples were measured by using a Perkin-Elmer 3110 atomic absorption spectrophoto-meter. Resistance frequency of the isolates was analyzed by agar dilution method. The highest resistances against all concentrations of all metals were found out Klebsiella sp. strains. Highest ratio of heavy metal resistance in the isolates was determined in 1 mM nickel (97 %), copper (88 %), cadmium (61 %) and chromate (25 %) concentration, respectively. No resistant bacteria was observed at 7 mM Cu and Cd and 5 mM Ni and Cr concentrations. These results suggest that releasing of urban and industrial wastewater into running surface waters without treatment processess increases the bacterial resistance against heavy metals. Therefore, the infectious diseases and heavy metal resistance are spreaded on large areas.